The Global Commonwealth of Citizens : Toward Cosmopolitan Democracy - Archibugi, Daniele (Book collections on Project MUSE., 2008)
The Global Commonwealth of Citizens critically examines the prospects for cosmopolitan democracy as a viable and humane response to the challenges of globalization. Arising after the collapse of the Soviet Union and the decisive affirmation of Western-style democracy, cosmopolitan democracy envisions a world politics in which democratic participation by citizens is not constrained by national borders, and where democracy spreads through dialogue and incentives, not coercion and war. This is an incisive and thought-provoking book by one of the world's leading proponents of cosmopolitan democracy.